2019
DOI: 10.1111/jdi.13117
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with diabetic polyneuropathy‐related sensory symptoms and signs in patients with polyneuropathy: A cross‐sectional Japanese study (JDDM 52) using a non‐linear model

Abstract: Aims/Introduction To assess the prevalence of diabetic polyneuropathy (DPN)‐related sensory symptoms/signs and associated factors in patients with polyneuropathy, considering non‐linear effects for numerical variables. Materials and Methods A cross‐sectional survey of patients with type 2 diabetes mellitus from 17 primary care clinics across Japan was carried out. DPN and DPN‐related sensory symptoms/signs were diagnosed according to the Diabetic Neuropathy Study Group in Japan criteria. Results Of the 9,914 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
3
8
1
1
Order By: Relevance
“…It is not known whether the higher prevalence of SS in women than in men was due to sex difference in the thresholds of sensory perception. A female preponderance of pDPN was also observed in the Korean study (7) and the Japanese study (10). Animal in vitro and in vivo studies suggested that estradiol may upregulate the nocisensor transient receptor potential (TRP) vanilloid 1 receptor in sensory neurons, resulting in lowered thresholds of sensation (28).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…It is not known whether the higher prevalence of SS in women than in men was due to sex difference in the thresholds of sensory perception. A female preponderance of pDPN was also observed in the Korean study (7) and the Japanese study (10). Animal in vitro and in vivo studies suggested that estradiol may upregulate the nocisensor transient receptor potential (TRP) vanilloid 1 receptor in sensory neurons, resulting in lowered thresholds of sensation (28).…”
Section: Discussionmentioning
confidence: 81%
“…In a cross-sectional study that aimed at investigating the prevalence of diabetic retinopathy in 1,008 diabetes patients enrolled from a hospital in Shijiazhuang, Hebei, China, the investigators reported a prevalence of 11% for DPN among the patients and found a close association between DPN and diabetic retinopathy ( 9 ). Another recently published cross-sectional study that enrolled patients from 17 primary care clinics across Japan showed a prevalence of 27.7% for DPN among 9,914 patients surveyed ( 10 ). Among the patients with DPN, 61.5% had DPN-related sensory symptoms/signs, which were significantly associated with female sex, smoking, and alcohol drinking ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic peripheral neuropathy (DPN) is a common complication of diabetes mellitus ( 1 ), with an estimated prevalence in patients with diabetes mellitus of 28% in the US ( 2 , 3 ), between 6% and 34% in Europe ( 4 ), and between 28% and 37% in Japan ( 5 - 7 ). Diabetic peripheral neuropathic pain (DPNP), one of the symptoms of DPN, is associated with numbness, pain, and abnormal sensation often occurring below the knees of both legs ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…La polineuropatía diabética es una de las complicaciones más comunes de la DM y su prevalencia es de aproximadamente 37 a 45% en personas con DM tipo 2 y 54 a 59% en personas con DM tipo 1 (9). En Francia, se describe que el 87% de los pacientes ingresados por pie diabético sufren de neuropatía y aún en centros especializados llegan a una tasa de amputación del 48% (10).…”
Section: Introduccionunclassified